The impact of Covid-19 on Domestic Violence and the Black, Asian and Minority Ethnic Community - Sapkota, Bindu Devkota; Simkhada, Padam; Wager, Nadia Marie (Europasian Journal of Medical Sciences, 2020)
The Coronavirus disease, also known as Covid-19, which is purported to have started in Wuhan, China, was declared a pandemic on 11th March 2020. In the UK, the government, together with the National Health Service (NHS), have taken various approaches to prevent and slow down the spread of coronavirus. These included imposing a ‘lockdown’ of the country (e.g. closure of schools, businesses, parks, leisure centres, and tourist attractions), along with the emphasis on handwashing, social distancing, the use of face masks and only permitting essential travel within the UK and between the UK and other countries. These approaches have been undertaken to varying extents and within different timeframes across the four nations of the UK. Like many other countries worldwide, the UK was not prepared for such pandemics which resulted in the inability to assess the most appropriate approach to contain the spread, including the availability of Personal Protective Equipment (PPE) for frontline workers, particularly those in health care. As the crisis continues several striking social issues have emerged which may, in part, be a consequence of the measures taken. These include the escalation in domestic violence (DV) and disproportionate burden of disease among the Black, Asian, and Minority Ethnic (BAME) community. The impact of Covid-19 may remain for a long time if appropriate measures are not put in place to address the health inequalities in time.